2011
DOI: 10.4065/mcp.2010.0762
|View full text |Cite
|
Sign up to set email alerts
|

A Plea for Caution: Violent Video Games, the Supreme Court, and the Role of Science

Abstract: On November 2, 2010, the US Supreme Court heard arguments in the case of Schwarzenegger v Entertainment Merchants Association, with a ruling expected in 2011. This case addressed whether states have the right to restrict freedom of speech by limiting the sale of violent video games to minors. To date, 8 states have tried to pass legislation to this effect, with all attempts being found unconstitutional by lower courts. In large part, the Supreme Court's decision will be determined by its review and interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…Nonetheless, the results were supportive of those of Van Looy et al in that it is not possible to claim that clinicians have reached a consensus of concern regarding the possible influence of video games on youth violence (H1). This is a particularly important finding as some scholars have observed that claims to the contrary, if discovered to be unfounded, can actually damage the reputation of the field as too alarmist rather than carefully objective (Hall, Day, & Hall, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, the results were supportive of those of Van Looy et al in that it is not possible to claim that clinicians have reached a consensus of concern regarding the possible influence of video games on youth violence (H1). This is a particularly important finding as some scholars have observed that claims to the contrary, if discovered to be unfounded, can actually damage the reputation of the field as too alarmist rather than carefully objective (Hall, Day, & Hall, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…And during periods of moral panic, society may incentivized harm-based conclusions from social scientists that distort initial research results (Gauntlett, 2005). Thus, patience in making conclusive statements about media effects may be key to reducing damage to the reputation of media psychology as a scholarly field (Hall et al, 2011).…”
Section: Practical Implications and Warning Biasmentioning
confidence: 99%
“…This preference for violent games was strongest in youth with externalizing disorders such as ADHD. Although controversial, 64,65 violent video games have been linked to increased aggressive behaviour, and decreased empathy and prosocial behaviour. 23,66 This increased exposure to violent video games in the psychiatric population is concerning, particularly as this is a vulnerable population with independent risk factors for aggression.…”
Section: Discussionmentioning
confidence: 99%
“…This includes using emotionally evocative labels for games, inflated rhetoric regarding the strength and consistency of effects, exaggerated press releases, and weak research designs (Ferguson 2013b;Hall et al 2011;. The violent video game field also appears to be touched by psychology's replication crisis, with direct replications of older studies ultimately failing to confirm previous results (e.g., Przybylski et al 2014;Nielson 2013, 2014) and suggestions of publication bias in the existing literature (Hilgard et al 2017).…”
Section: A Way Forwardmentioning
confidence: 53%